Ground-penetrating radar investigation of the cylindrical pedestal of a monument - Bonomo, Nestor Eduardo (2015)
We describe a GPR methodology used to investigate the internal structure of three consecutive sections of the cylindrical pedestal of a monument that had to be disassembled for relocation. We acquired constant-offset circular profiles and non-standard variable-offset profiles at different heights along the pedestal. In the raw data sections, the reflections of interest were hidden by significant environmental noise with frequencies that overlapped those of the transmitted pulses and varied from trace to trace. We successfully eliminated the noise by iteratively fitting sinusoidal waves in different x–t windows and by subtracting the results from the traces. The resulting sections were interesting because they exhibited numerous and varied reflections. We analysed these sections using a combination of procedures previously used for cylindrical structures and other procedures adapted from protocols commonly used for plane semi-spaces. In particular, we evaluated the information provided by the variable-offset profiles and determined how it complemented the information obtained from the constant-offset profiles. In the variable-offset profiles, multiple reflections produced at the cylinder–air interface were reliably distinguished up to the fifth-order of reflection by taking advantage of their distinctive shapes. In the constant-offset profiles, this information was used to distinguish the multiples from possible signals of internal structures or their multiples and from unwanted signals produced by the GPR system, which can be confused with the multiples. We also considered obtaining the propagation velocity across the structure with a high degree of reliability by including the travel times of higher-order multiples in the calculations. Fitting of the theoretical curves, migration and polar representations allowed for a thorough interpretation of the reflectors present in the structures. Probable reinforcement bars, circular ties, natural veins of the material and reflectors located in nearby sections of the monument were identified. The continuity of the reflectors along the pedestal was determined. On this basis, an efficient disassembly and relocation plan for the monument was designed and performed.